Reverse Z-effect phenomenon in a basicervical femoral fracture using cephalomedullary nail with two superior antirotation screws: A case report and procedure evaluation. (February 2021) - Tabata, Yusuke; Matsui, Shuhei; Miyamoto, Masabumi; Nakajima, Takao; Majima, Tokifumi
Abstract: We present a case of reverse Z-effect phenomenon in a basicervical femoral fracture using a cephalomedullary nail together with two superior antirotation screws and evaluate the procedure. An 86-year-old woman fell in her home and could not stand due to right hip joint pain. X-ray and CT imaging showed a right basicervical femoral fracture (AO/OTA classification; 31B3), and open reduction and internal fixation (OR/IF) was performed with a cephalomedullary nail and two superior antirotation screws (TES Nail, HOMS, Tokyo, Japan). Two months later, X-ray showed penetration of the femoral head by the inferior lag screw with lateral migration of the two superior antirotation screws; the so-called "reverse Z-effect"; without any trauma. We performed the exchange of a shorter inferior lag screw for the longer one, and replaced the sliding type end cap with one of rocking type. The reverse Z-effect has been reported in cases with two lag screws, i.e. one inferior and one superior, in the past; however, to our knowledge, there has been no case reported in the literature using two superior antirotation screws together with one inferior lag screw.